2015
DOI: 10.1186/s12967-015-0503-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of cohesin loading factor NIPBL confers poor prognosis and chemotherapy resistance in non-small cell lung cancer

Abstract: BackgroundNIPBL, the sister chromatid cohesion 2 (SCC2) human homolog, is a cohesin loading factor which is essential for deposition of cohesin onto the sister chromatid. Recent studies have shown that NIPBL contribute to sister chromatid cohesion and plays a critical role in development, DNA repair, and gene regulation. In this study, we measured the expression of NIPBL in clinical non-small cell lung cancer specimens, and determined its effects on cellular processes and chemosensitivity in vitro.MethodsNIPBL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 42 publications
3
17
0
Order By: Relevance
“…The relationship between CDRC expression pattern and clinicopathologic parameters was evaluated. The results indicated that increased DNA repair capacity was correlated with poor tumor differentiation and poor survival 29 30 , which was also validated in the independent cohort. However, interestingly, intrinsic HCC subtypes by CDRC were not contingent on tumour stage or other single clinicopathologic parameter.…”
Section: Discussionsupporting
confidence: 56%
“…The relationship between CDRC expression pattern and clinicopathologic parameters was evaluated. The results indicated that increased DNA repair capacity was correlated with poor tumor differentiation and poor survival 29 30 , which was also validated in the independent cohort. However, interestingly, intrinsic HCC subtypes by CDRC were not contingent on tumour stage or other single clinicopathologic parameter.…”
Section: Discussionsupporting
confidence: 56%
“…For example, Xu et al 51 showed that enhanced RAD21 expression confers poor prognosis and drug resistance in high grade luminal, basal and HER2+ breast cancers, while Deb and colleagues 52 showed that RAD21 overexpression is predictive of poor prognosis in KRAS mutant colorectal cancers. In addition, enhanced NIPBL expression is associated with poor prognosis and chemotherapy resistance in non-small cell lung cancer 53 , while SMC1A overexpression contributes to colorectal cancer development in a mouse model 54 . While speculative, these findings, coupled with data from the current study strongly suggest that cohesion gene expression is normally tightly regulated, and that deviations, either through gene copy number losses or gains, may be etiological events contributing to the development and progression of cancer, although this remains to be empirically determined.…”
Section: Discussionmentioning
confidence: 99%
“…Another molecule that is strongly predicted to be a target of miR-410 is NIPBL. NIPBL (Nipped-B-like protein), also known as delangin or SCC2 homolog is a marker for poor prognosis and promotes chemotherapy resistance ( 46 ). As we have previously discussed, metastatic neuroblastomas show little to no expression of SPARC and SPARC overexpression is known to induce expression of miR-410 by a yet unknown mechanism.…”
Section: Discussionmentioning
confidence: 99%